(3QSGdI aj GdTcd hGdbWGYs - (3KGHJ Hf bQI Hf RgQhf GdMQGfj GdUCHrj, CHh GdMSf,J (B288 (3g` s
(3ChdgG (B:s
(3ageJ CSYOc Gddg eG bdJg ai GdTcd GdedbH HGdbWGY heG SCdJ Yfg ef CeQg heG CYde Cf TjFkG ef GGdCTcGd GdgfOSjI GdeSJYedI ai Yde GdfLhe NGV GdfGS ajg NhVge ai gPG GdTcd s
(3BNQgG (B:s
(3ajchf LedI GdhLhg KeGfjI YTQ hLgkG hNdGaGJgG abW dg Cbd ef Pdc hdG CcKQ JeJ GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfi YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B98 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B101s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs